Jewish Wife Repudiates Her Husband - Lipiński, Edward (Anabasis. Studia Classica et Orientalia, 2015)
The wife’s right to initiate the divorce and to repudiate her husband is attested by Near Eastern documents from the early second millennium B.C. on and it is implied by Ex. 21:7–11, where ’āmāh possibly designates a second-rank wife. This right is clearly formulated in the Jewish Aramaic marriage contracts from Elephantine, which follow a Near Eastern tradition, and it is attested by the legal repudiation of the husband by his wife, written on a papyrus found in the Judaean Desert. The document answers the requirements of such acts: it contains the declaration of divorce, a renunciation to belongings which correspond to the divorce money; it is dated and names the witnesses. The text dates from A.D. 135 and is thus somewhat posterior to the divorce bills sent to their husbands by women belonging to the Herodian family. The wife’s initiative in divorce matters is still well represented in texts from the Cairo Genizah, dated about the 10 th century A.D.